Don't Risk It. Older Adults Perceive Fewer Future Opportunities and Avoid Social Risk Taking. (March 2021) - Delaney, Rebecca K.; Strough, JoNell; Shook, Natalie J.; Ford, Cameron G.; Lemaster, Philip
Drawing from life-span psychology, we conducted two studies to test perceptions of time left in the future as an underlying mechanism for age differences in self-reported social risk taking. Study 1 included 120 younger (25–35 years) and 119 older (60–91 years) community-dwelling adults. Study 2 included 439 participants (18–85 years) mostly recruited from Amazon Mechanical Turk. In both studies, older age was associated with rating a lower likelihood of social risk taking (e.g., speaking about an unpopular issue) and perceiving the future as holding fewer future opportunities and being more limited. Perceptions of fewer future opportunities with aging statistically mediated age-related declines in social risk taking. Findings highlight motivational factors as key for understanding age differences in social risk taking. Implications of age differences in social risk taking on factors related to well-being, such as social support and strain, are discussed.